Nitrogen uptake and utilization of two maize hybrids with contrasting nitrogen use efficiencies depending on fertilization amount. Issue 11 (19th September 2023) - Shao, Guodong; Cheng, Hao; Dai, Hongcui; Zhang, Hui; Ai, Juanjuan; Liu, Kaichang; Li, Zongxin; Zamanian, Kazem; Qian, Xin
ABSTRACT: Splitting nitrogen (N) application is beneficial for achieving higher grain yields and N use efficiency (NUE), but the responses of N utilization efficiency of different maize cultivars to top-dressing N fertilizer rates are still unclear. This study investigated the effects of fertilization managements on N uptake and utilization derived from topdressing fertilizers of maize hybrids (Ludan981 and Denghai605) with contrasting NUEs. The N fate derived from topdressing fertilizer was determined using the 15 N tracing method. Grain yields, dry matter and N accumulation of both maize hybrids were significantly increased under low N levels but decreased under high N levels. Under N-deficient and excess conditions, Denghai605 had higher NUE than Ludan981. The N rates of topdressing significantly affected N uptake and utilization, but no difference was detected between two maize hybrids, and excessive N use led to higher rates of N loss and residual in soil. The N metabolism enzyme activities did not differ between the two maize hybrids. Our findings suggest optimized N management strategies by adjusting topdressing N application rate and timing are necessary to increase NUE and to minimize environmental costs in maize cropping system.